Optimal design of inter-plant water network with centralized regeneration system - Hazlinda, Sapee (2012)
Water is a basic raw material in an industry.Without it, the production cannot run or will be hindered.But,nowadays we are lacking reliable sources of water.In the future,two thirds of the world population will face water crisis or stress by the year 2025.In 2025,industrial growth will rapidly speed up hence the sources of water will be limited. The negative effect of lack of sources of water make the cost of the water will be increasing.Hence,a new model has been developing based on water network superstructure to simultaneously generate the maximum water recovery targets and design minimum water network.Nowadays,water system integration becomes the research focus,because the technology is effective for saving fresh water and reducing wastewater generation.The purpose of this study is to develop a systematic technique for designing the minimum water network for inter-plant with centralized regeneration system.This problem is formulated as mixed integer nonlinear programming (MINLP)based on water network superstructure and is implemented in Generalized Algebraic Modeling System (GAMS) in order to obtain simultaneous minimum water targets and design of water networks.The effectiveness of the proposed model is illustrated by using an industrial case study.A significant reduction of fresh water consumption and waste water generation has been achieved,illustrating the effectiveness of the proposed approach.The result show the potential maximum freshwater and wastewater reduction are 53.63% and 61.65% respectively.